Influence of fins designs, geometries and conditions on the performance of a plate-fin heat exchanger-experimental perspective - M.I.N, Ma'arof; Girma, T. Chala; Hazran, Husain; Muhammad S., S.Mohamed (Universiti Malaysia Pahang, Malaysia, 2019)
A fin heat exchanger is a simple form of cooling device that is built for efficient heat transfer from one medium to another. Generally, it involves medium such as fluid to perform heat exchange via convective heat transfer. This study is aimed at investigating the effects of diverse designs (arrangements of the fins), qualities (the total surface area of the fin for heat exchange) and conditions (the surface characteristics) of fin heat exchanger on the degree of heat transfer from the experimental perspective. The fin heat exchanger was fabricated and tested. It was observed that by varying the arrangement and condition of the fins, the rate of heat transfer could be affected. However, varying the quality of the fin didn’t have much impact. Nevertheless, the quality aspect of the fin heat exchanger could play a significant role for heat exchanger of larger in scale and dimension. The coating, that is the condition of the fins, aided in decreasing the temperature at a much higher margin at all fan speeds.